Physical Factors of Beetroot Seed Presowing Treatment Affect Sowing Quality and Crop Yield - Shevchenko, Nadiia; Kovalenko, Galyna; Bashtan, Natalia; Mozgovska, Anna; Miroshnichenko, Tatiana; Strybul , Tamara; Ivchenko, Tatiana; Kuts, Oleksandr (Problems of Cryobiology and Cryomedicine, 2022)
In this work, we have studied the impact of ozonation, freezing down to liquid nitrogen temperature and their combination on sowing quality and crop yield for Dii cultivar beetroot seeds. The optimal moisture, ozone dose within the ozone-air mixture, and the exposure time, not reducing the germination rate, were determined. The ozonation, freezing, and their combined effect affected neither the seed germination in laboratory, nor biometric indices in a field. The seed freezing down to liquid nitrogen temperature was found to significantly increase its crop yield. Biochemical analysis of root crops showed all the ways of presowing treatment to reduce the content of total sugars and betanine. After freezing and ozonation, the amount of dry matter decreased, but after combined exposure it augmented. Ozonation and subsequent freezing lowered the content of ascorbic acid. Signifi cantly reduced studied parameters did not reach the minimum values specific to this crop. Freezing and a combined impact of the studied factors on the seeds increased the nitrate content in root crops, which did not exceed the maximum allowable rate. Probl Cryobiol Cryomed 2022; 32(3):183–195